Volatility and Transmission of Palm Oil Price in The Province of North Sumatera and Bengkulu Province - Herdiyanti, Yulia; Sukiyono, Ketut; Irawan, Andi (International Journal of Oil Palm, 2023)
This study aims to analyze the level of volatility and transmission of palm oil prices in the Rotterdam and Belawan markets as well as the price of palm FFB in the markets of North Sumatera and Bengkulu Provinces. This study uses time series data for 120 months from January 2012 to December 2021. In this study, the data analysis method used to analyze the level of price volatility is Autoregressive Conditional Heteroscedasticity-Generalized Autoregressive Conditional Heteroscedasticity (ARCH-GARCH) and to analyze the level of price transmission is Autoregressive Distributed Lag (ARDL). The results showed that 1) the price volatility level in the Rotterdam and Belawan palm oil markets was high, 2) palm oil price transmission which is perfectly transmitted both in the short term and in the long term only occurs between the Rotterdam palm oil market and the Belawan palm oil market.